Sexual Politics and Stateâ€™s Indifference to Sexual Violence in Indonesia - Irawaty, Diah (Yayasan Jurnal Perempuan, 2016)
How does not the government that represents the state show a strong commitment and responsibility to ending sexual violence? Why does the state choose to engage more in giving â€œtemporary responseâ€ to the cases of sexual violence? If the state appears to play a systematic role in ending sexual violence, why does not the agenda really address patriarchal structure as the root of sexual violence? This article discusses how the stateâ€™s politics of sexuality in Indonesia that was mainly propagated during the New Order administration plays a pivotal role in the irresponsible way the state and the society deal with sexual violence.